The implementation of the Model Law on Cross-Border Insolvency: International divergences and challenges ahead - Aurelio GURREA-MARTINEZ, (Institutional Knowledge at Singapore Management University, 2024)
The Model Law on Cross-Border Insolvency (‘MLCBI’) was enacted by the United Nations Commission on International Trade Law (‘UNCITRAL’) in 1997. Since then, it has been adopted by 62 jurisdictions and has led to many debates and interpretations about its potential, scope and limits. This article provides a general overview of some of the international divergences existing in the implementation of the MLCBI across jurisdictions. It also discusses some of the challenges that need to be overcome to make the MLCBI a more effective tool to deal with cross-border insolvency.